IS PLAGUE GLOBALLY REEMERGING? - Alfonso Rodriguez-Morales (Asociación Colombiana de Infectología, 2019)
Emerging and reemerging diseases are cause of concern for the World Health Organization (WHO). On February 2018, WHO releases its list of priority pathogens that have the potential to cause a public health emergency, given that for them there is no, or is insufficient, countermeasures, such as drugs and vaccines that help control outbreaks. During the last years, the world has experienced recent significant outbreaks of plague, an infection caused by Yersinia pestis and transmitted by fleas. In Africa, Madagascar,2-4 suffered during 2017 an outbreak, from the August 1 through November 22, 2017, with a total of 2348 confirmed, probable and suspected cases, including 202 deaths (case fatality rate [CFR] 8.6%). There were 1791 cases of pneumonic plague, of which 22% were confirmed,